Visual outcome of standard treatment of sarcoid uveitis at a tertiary eye center in Nepal - Subedi, Kumudini; Shrestha, Smita; Poudel, Manish; Manandhar, Anu (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Sarcoidosis is a less-studied disease in Nepal, both as a systemic as well as ocular disease. We aimed to describe the visual outcome of standard therapy of sarcoid uveitis in Nepal.Methods: Observational study through Electronic Medical recording system of Tilganga Institute of Ophthalmology from December 2017 to March 2020. Patients diagnosed by IWOS criteria, treated with standard protocol and with minimum six-month follow up were included. The clinical parameters evaluated were type of uveitis, anatomical location and IWOS category. Treatment related factors evaluated were need for immunosuppressants, anti-glaucoma medication and cataract surgery. Visual outcome at six months was the major outcome evaluated, considering two lines of improvement or worsening as significant. Vision limiting complications assessed were cystoid macular edema, complicated cataract and secondary glaucoma. Visual outcome was stratified based on demography, anatomical involvement, uveitis subtype, IWOS category and need for immunomodulators.Results: Forty-six eyes of 25 patients were included. Based on IWOS criteria, presumed ocular sarcoidosis had best visual outcome with 93.33% improvement. Males had better post-treatment vision (90% vs.76.9%). 20-40 years age group had best improvement (96.5%) and anterior uveitis had best visual outcome (100%). A single immunomodulator could not be recommended based on this study. 18(39%) eyes had raised IOP, 4(8.6%) had secondary angle closure glaucoma, 4(8.6%) had hypotony, 1(2.1%) eye underwent cataract surgery and 1(2.1%) eye had cystoid macular edema.Conclusions: Sarcoid uveitis has good visual outcome. High degree of suspicion, early diagnosis and prompt treatment aids in diagnosis and limits vision-limiting complications.